1995
DOI: 10.1016/s0022-5223(05)80018-2
|View full text |Cite
|
Sign up to set email alerts
|

Detection of primary and recurrent lung cancer by means of F-18 fluorodeoxyglucose positron emission tomography (FDG PET)

Abstract: Positron emission tomography (PET), with the glucose analog F-18 fluoro-deoxyglucose (FDG), takes advantage of the enhanced glucose uptake observed in neoplastic cells. We examined whether the detection of preferential FDG uptake with PET permits differentiation between benign and malignant focal pulmonary lesions in patients with suspected primary or recurrent lung cancer. Between November 1991 and September 1993, 100 patients with indeterminate focal pulmonary abnormalities including 16 patients who had prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
60
0
5

Year Published

1996
1996
2009
2009

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 188 publications
(66 citation statements)
references
References 7 publications
1
60
0
5
Order By: Relevance
“…These factors then determine how we should decide who could benefit from a PET study and once the test has been performed how the result could influence management. Given the excellent performance parameters that we identified-a likelihood ratio of 9.9 for a positive PET read as ''definitely malignant'' and a likelihood ratio of 0.03 for a negative PET read as ''definitely benign''-it is still unlikely that patients with either a very low (5%) or very high pretest probability (.80%) of a malignant solitary pulmonary nodule would benefit from this examination (2). In a cost-effectiveness analysis of 18 F-FDG PET in solitary pulmonary nodules, Gould et al reached similar conclusions and indicated that 18 F-FDG PET should be used selectively when pretest probability and CT findings are discordant or in patients COPYRIGHT ª 2009 by the Society of Nuclear Medicine, Inc.…”
Section: To the Editormentioning
confidence: 90%
See 1 more Smart Citation
“…These factors then determine how we should decide who could benefit from a PET study and once the test has been performed how the result could influence management. Given the excellent performance parameters that we identified-a likelihood ratio of 9.9 for a positive PET read as ''definitely malignant'' and a likelihood ratio of 0.03 for a negative PET read as ''definitely benign''-it is still unlikely that patients with either a very low (5%) or very high pretest probability (.80%) of a malignant solitary pulmonary nodule would benefit from this examination (2). In a cost-effectiveness analysis of 18 F-FDG PET in solitary pulmonary nodules, Gould et al reached similar conclusions and indicated that 18 F-FDG PET should be used selectively when pretest probability and CT findings are discordant or in patients COPYRIGHT ª 2009 by the Society of Nuclear Medicine, Inc.…”
Section: To the Editormentioning
confidence: 90%
“…The data presented in the article, however, also address an even more controversial clinical issue, namely: what is the visual or standardized uptake value (SUV) cutoff for classifying a solitary pulmonary nodule as benign? The traditional teaching, supported by numerous early, pivotal studies, including several by the authors of this paper, is that nodules with an SUV less than 2.5 or whose activity appears visually to be less than or equal to that of the mediastinal blood pool can be considered benign with enough confidence to avoid an immediate biopsy; these nodules can safely be followed with CT (2,3). Recently, several groups have published data contradicting this principle (4), including evidence that any visually perceptible uptake by a pulmonary nodule is associated with a significant chance of malignancy (5).…”
Section: To the Editormentioning
confidence: 96%
“…Knopp [124,125]. Others have also reported a high diagnostic accuracy of FDG PET in the detection of tumour recurrence [113,[126][127][128][129][130].…”
Section: Fig 2 Malignant Solitary Pulmonary Nodule (Adenosquamous Cmentioning
confidence: 99%
“…FDG-PET has thus been studied extensively as a promising noninvasive imaging test to differentiate between benign and malignant nodules [27][28][29][30][31][32][33][34][35][36][37]. Based on 12 well-designed prospective studies, it can be concluded that FDG-PET has proven to be accurate in differentiating benign from malignant lesions as small as 1 cm [21].…”
Section: Diagnosis Of Solitary Lung Nodule or Massmentioning
confidence: 99%
“…Therefore, falsenegative findings can occur in lesions v1 cm [29,30,34,35,38], in tumours with low metabolic activity (e.g. carcinoid tumours [30,39]), or in bronchioloalveolar cell carcinoma [38,[40][41][42].…”
Section: Diagnosis Of Solitary Lung Nodule or Massmentioning
confidence: 99%